Spectator no more, the role of the membrane in regulating ion channel function - Pliotas, C; Naismith, J (Elsevier, 2016)
A pressure gradient across a curved lipid bilayer leads to a lateral force within the bilayer. Following ground breaking work on eukaryotic ion channels, it is now known that many proteins sense this change in the lateral tension and alter their functions in response. It has been proposed that responding to pressure differentials may be one of the oldest signaling mechanisms in biology. The most well characterized mechanosensing ion channels are the bacterial ones which open when the pressure differential hits a threshold. Recent studies on one of these channels, MscS, have developed a simple molecular model for how they sense and adapt to pressure. Biochemical and structural studies on mechanosensitive channels from eukaryotes have disclosed pressure sensing mechanisms. In this review, we highlight these findings and discuss the potential for a general model for pressure sensing.